AI-assisted Food Ordering and Delivery Management System for KFC: Insights from Malaysia, Indonesia and India - Liem, Gai Sin; Koay, Loke Kean; Sanderan, Padmavathy A/P; Pong, Hui Ling; Poon, Zi Ying; Marimuthu, Sahliny A/P; Gisca, Aulia Purdiana; Gupta, Manshi; Saxena, Mansi; Kee, Daisy Mui Hung (AIBPM Publisher, 2023)
AI-assisted food ordering and delivery management systems is a revolutionary technology which aims to improve the ordering and delivery process of food by incorporating artificial intelligence. Hence, most of the restaurant owners had implemented AI-assisted food ordering and delivery management systems for improving the business efficiency and customer satisfaction. The objective of this paper is to evaluate how the AI-assisted service can create efficient planning and better customer satisfaction, predict consumer behavior which can save time and wastage of products for the restaurants. There were 100 respondents who participated in the online survey. The study and findings indicate that perceived convenience, reliability, price, ease of use, enjoyment, trust, social influence, and attitude influence consumers' behavioral intentions for food delivery services. Subsequently, this research contributes to a deeper understanding of the AI-assisted food ordering and delivery management system for restaurants. Recommendations and consequences were presented.